Síntese ambientalmente sustentável e aplicação fotovoltaica de pontos quânticos Cu-In-S e Zn-Cu-In-S - Josué Coelho do Amaral Júnior (2021)
The use of fossil fuels as an energy source has resulted in great social, environmental and economic costs, making the search for alternative energy sources one of the main priorities of modern society. Solar energy stands out as a solution to this problem as an unlimited source of clean energy with high availability on the Earth's surface. Thus, the present work developed Cu-In-S quantum dots, for photovoltaic applications, synthesized through an aqueous colloidal route at room temperature and stabilized using the renewable polysaccharide, carboxymethylcellulose, as a binding agent. In order to control and adjust the properties of these nanoparticles, variations were made in the composition, copper content and Indium: sulfur ratio, and in the heat treatment time. In addition, to promote passivation surface defects harmful for the performance of these quantum dots, ZnS deposition was performed onto the Cu-In-S nucleus, forming Zn-CuIn-S quantum dots. The nanoparticles were characterized by transmission electron microscopy, ultraviolet-visible absorption spectroscopy, photoluminescence, 3D photoluminescence, dynamic light scattering, Zeta potential, Fourier transformed infrared spectroscopy, X-ray fluorescence, X-ray photoelectron spectroscopy and quantum yield. The results showed the formation of nanoparticles with monodisperse size distribution with average diameters of 3.7 nm and 4.9 nm for Cu-In-S and Zn-Cu-InS, respectively, with absorption at the wavelengths from 300 nm to 600 nm, and emission from 500 nm to 900 nm, and maximum quantum yield of 6.2%. To assess the feasibility of photovoltaic application, photoelectrodes of TiO2 sensitized with quantum dots Zn-CuIn-S were produced, and characterized photoelectrochemically using linear voltammetry. The sensitization process with Zn-Cu-In-S quantum dots resulted in gains of up to 780% in the photogenerated current density and in the efficiency of energy conversion under illumination in the visible spectrum, proving the viability of using these quantum dots in photovoltaic applications.